A comparison of heating terminal units: Fan-coil versus radiant floor, and the combination of both - Atienza-Márquez, Antonio; Fernández-Hernández, Francisco Ángel; Domínguez-Muñoz, Fernando; Carrillo-Andrés, Antonio; Cejudo-López, José Manuel (Elsevier, 2017)
Several control strategies are compared for a hydronic heating system that combines two different terminal units, radiant floor and fan-coil, in the same thermal zone. The performance of the combined system is evaluated in terms of energy consumption and comfort level. The production unit is an air-water heat pump. Four control strategies are defined and compared using a TRNSYS model: one strategy is applied when only the radiant floor operates, two strategies (simply and improved) are applied when only the fan-coil operates, and one strategy is applied when both terminal units operate simultaneously. Simulations are undertaken for three major cities with different heating requirements. In terms of comfort, the combined system achieves the higher scores, ensuring comfort conditions during most of the heating season. In terms of energy consumption, the worst option is the one that uses a fan-coil with fixed air velocity and fixed inlet water temperature. Nonetheless, there are not important differences between the analysed control options. The energy consumption of the system is mainly influenced by the part load performance of the heat pump, although the differences are small.
Keywords: Calefacción por agua caliente; Radiant floor; Fan-coil; Control; Heating combined system